"Tortured Women and Hungry Widows": Patriarchal Neoliberalism and the Logic of Compensational Justice in Chile. (May 2013) - Macias, Teresa
This article explores how parliamentary debates in postauthoritarian Chile discursively produced and deployed feminized images of victims and survivors of the authoritarian regime to sustain the constitution and establishment of a logic of compensational justice. In describing and delineating the gender politics of representation in these social policy debates, the article also looks at how compensatory justice is constituted along the lines of a neoliberal market mentality. In this way, the article traces how patriarchal power relations and neoliberal governmental rationality are mutually constitutive regimes that require the real and imagined bodies of women as a surface of inscription.